Analisis Pengaruh Temperatur dan Durasi Preheat terhadap Cacat Produk pada Mesin Injection Molding Manual - Apriawan Nur Huda; Ignatius Aris Hendaryanto; Benidiktus Tulung Prayoga; Agustinus Winarno (Jurnal Engine: Energi, Manufaktur, dan Material, 2024)
Plastic objects are widely used and found in all places, from food packaging, household appliances, and electronic devices to vehicles. Generally, plastic is used as a substitute for glass, wood, and metal. Over time, the use of plastic has become an environmental issue. To address the problem of plastic waste, the government has introduced the 3R (Reduce, Reuse, and Recycle) initiative. One of the easily used tools in the recycling process is the injection molding machine. This process often results in product defects such as Short Shot, Flow Mark, and Sink Mark. The temperature in the injection process affects the melting point of the plastic and can influence various aspects of the manufacturing process and the final quality of plastic products. The heating duration affects the viscosity of the plastic material to be injected. The research conducted is experimental, and several tests were performed to determine the effect of temperature variation and preheat duration of the injection molding machine on product quality. Simulation results show that the higher the temperature used, the greater the resulting sink marks. The test results indicate that improper temperature and preheat duration usage will affect the occurrence of product defects. A temperature that is too low can result in high pressure during the injection process, preventing the material from filling the cavity maximally. Preheat duration and temperature are critical factors in the plastic manufacturing process, affecting melting points, flow quality, dimensional stability, and the mechanical properties of the final product. Proper control of heating duration, temperature, and other process conditions is essential to produce high-quality, defect-free plastic products. Keywords: Injection Molding, Preheat, Temperature